Aspekty słowotwórcze pseudoetymologicznej gry językowej - Miakiszew, Władimir (Studia Rossica Posnaniensia, 2018)
The paper addresses B. Norman's humorous etymological Russian dictionary. By reanalyzing the morphological structure of Russian words, Norman provides them with knowingly false, amusing interpretations. The paper proposes to investigate the word-formation aspects of Norman’s re-analyzed lexis. It mostly represents an attempt to “build” the false etymological entities into the system of all existing word-formation techniques of the Russian language. Specific features of amusing para-etymology are also identified.